Black Soldier Fly Larvae Meal in the Diet of Gilthead Sea Bream: Effect on Chemical and Microbiological Quality of Filets - Oteri, Marianna; Chiofalo, Biagina; Maricchiolo, Giulia; Toscano, Giovanni; Nalbone, Luca; Lo Presti, Vittorio; Di Rosa, Ambra Rita (Frontiers in Nutrition, 2022)
Chemical and microbiological characteristics of the fillets of Spaurus aurata L. specimens fed diets containing Hermetia illucens meal (HIM) at 25%, 35% and 50% levels, as a partial replacement for fish meal (FM), were evaluated. Diets, formulated to satisfy the nutritional needs of fish, were isoenergetic (22 MJ/kg gross energy), isonitrogenous (43 g/100g, a.f.) and isolipidic (19 g/100g, a.f.). Seventy-two specimens were randomly killed after 186 days of growing trials. Then, the fillets were analyzed for chemical profile, fatty acids, aminoacids, minerals and microbial flora. Data were subjected to the statistical analysis. No significant differences were observed for the chemical composition. The sum of polyunsaturated fatty acids (PUFA) showed a similar content in the fillets; the eicosapentaenoic acid was similar in the fillets of HIM0, HIM35% and HIM50% whereas, the docosahexaenoic acid was higher in the fillets of HIM0 group. The n3/n6 PUFA ratio and the sum of EPA+DHA showed a higher (p<0.001) value in the fillets of the group fed FM. No significant difference was observed for thrombogenic index and hypocholesterolaemic/hypercholesterolaemic ratio in the groups; the atherogenic index showed a higher (p=0.001) value in the HIM50% group. Indispensable amino acids showed some significantly (p<0.0001) differences in the groups; arginine and phenylalanine content were higher in the fillets of fish fed FM; isoleucine and valine content was higher in the fillets of HIM50%; leucine, lysine and methionine content was lower in the fillets of HIM35%; histidine content was lower in the fillets of HIM25% and tryptophan in the fillets of HIM50% group. The EAA/NEAA ratio showed the highest value in the fillets of the group receiving FM. The presence of HIM in the three diets kept chromium, manganese, iron, copper, zinc and nickel levels lower than those recommended by various authorities. The Ca/P ratio showed a higher (p<0.0001) level in the group fed FM than those fed diets containing HIM. Insect meal into the diets did not influence the microbiological profile of fish. Use of HIM as unconventional feed ingredient in Sparus aurata diet looks promising, although the quality of the fillets may be affected.